The intercultural adaptation experience of Afghan students in Malaysia - Ahmad, Abdul Latiff; Azimi, Hameedullah; Salleh, Sabariah; Mohamad, Emma Mirza Wati; Sannusi, Shahrul Nazmi (2017)
Studying abroad is an experience which can benefit both students’ original and host countries. The Afghan government in their quest to improve the human capital have decided to send their students to pursue their studies abroad.It is hoped that these students not only succeed in their academic endeavor but also to learn from the context of cultural and social experience of others, of the technological and globalising world; and bring the rich experience home to help develop the country. The research uses the U-Curve model of intercultural adjustment (Lysgaard, 1955) as the foundation which describes adaptation as a process that moves from a “honeymoon” period into “culture shock” and on to recovery or “adjustment” and “mastery” stages. It looks at the experiences of Afghan students in their adaptation process. Data were obtained from three focus groups discussion done at three different public universities in Malaysia that enrolled the Afghan students. Studies showed that though students went through a bit of culture shock earlier, they are able to adapt in the end which is similar as to the stages discussed in the model.